Does counter-terrorism work? - English, Richard (Oxford University Press, 2024)
State responses to terrorism have shaped politics and society globally. But how far, and in what precise ways, has counter-terrorism actually succeeded? Based on the author's experience of studying terrorism and counter-terrorism for over three decades, Does Counter-Terrorism Work? offers an historically-grounded, systematic, and expert interrogation of the effectiveness of state responses to terrorist violence. Previous analyses have too often tended to be polarized, simplistic, and short-termist; they have also lacked a comprehensive framework against which properly to assess the (in)efficacy of counter-terrorist efforts over time. Richard English's pioneering book carefully defines what effective counter-terrorism would involve, and then tests that layered framework through cross-case, balanced, historically-focused comparison of important counter-terrorist campaigns. Drawing on a vast range of source material, Does Counter-Terrorism Work? assesses in detail the strategic, tactical, and personal or political achievements and failures evident this blood-stained field of work.